2019
DOI: 10.1002/cnma.201900157
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Deficiency Driven Conversion of Polysulfide by Electrocatalysis: MoO3‐x Nanobelts for an Improved Lithium‐Sulfur Battery Cathode

Abstract: Despite a high energy density and specific capacity, the commercial implementation of lithium‐sulfur batteries still suffers from a severe polysulfide shuttle. Numerous efforts have been made to confine polysulfide species through physical adsorption and chemical bonding. Nevertheless, polysulfide accumulation is also ascribed to the slow redox kinetics. Herein, we design a kind of MoO3‐x nanobelt with abundant engineered oxygen defects (ODs) on the surface to promote the redox kinetics as a cathode matrix for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…This tunnel-like structure accommodates oxygen deficiency via oxygen vacancies and crystallographic shear planes. The formation of an intermediate compound Mo m O 3m−1 between Mo VI O 3 and Mo IV O 2 during the reduction of MoO 3 has been reported many times [15,45,46], but here, despite the previous claims, we obtained a stable phase with the O/Mo ratio of 2.8.…”
Section: Discussioncontrasting
confidence: 75%
“…This tunnel-like structure accommodates oxygen deficiency via oxygen vacancies and crystallographic shear planes. The formation of an intermediate compound Mo m O 3m−1 between Mo VI O 3 and Mo IV O 2 during the reduction of MoO 3 has been reported many times [15,45,46], but here, despite the previous claims, we obtained a stable phase with the O/Mo ratio of 2.8.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition to cation vacancies, anion vacancies of metal oxides, metal sulfides, and metal nitrides can also be active sites for firmly capturing polysulfides and significantly improving their redox reaction. For instance, Lin et al proposed the effects of oxygen deficiency on the conversion reactions of polysulfides by using oxygen‐deficient WO 3 as the model compounds .…”
Section: Defective Electrode Materials For Rechargeable Batteriesmentioning
confidence: 99%
“…Nazar and co‐workers proved the formation of thiosulfate and polythionate by the reaction between LiPSs and MnO 2 nanosheets, which served as a redox shuttle to inhibit LiPSs dissolution into the electrolyte and transform them into insoluble Li 2 S 2 or Li 2 S. Long and co‐workers proposed that the formation of thiosulfate and polythionate was further accelerated by introducing OVs into the hollow MnO 2 nanospheres, which provided modified electrochemical performance than pristine MnO 2 for LSBs. [ 143 ] Integration of multi‐metal component in one crystal is highly expected to tune LiPS transport and regulate Li 2 S deposition, since it potentially combines individual component functions. It has been revealed that the niobium oxide with oxygen vacancies (Nb 2 O 5− x ) could promote the affinity with LiPS and accelerate the kinetics of sulfur conversion reaction.…”
Section: Emerging Metal‐based Catalytic Materials For Li–s Batteriesmentioning
confidence: 99%